Wujud Nyata Peduli Sosial dalam Aksi Partisipatif Warga Kota Makassar untuk Kemanusiaan dan Keselamatan - Nur Utaminingsih; Lily Yulianti Farid; Nur Isdah; Ita Ibnu; Ayu Kartika Julia T. (RUANG KOMUNITAS: Jurnal Pengabdian Masyarakat, 2023)
This article describes the independent initiatives of Makassar residents from various backgrounds, most of whom have been diaspora in various big cities worldwide. Empathy as fellow citizens sees the dynamics of handling Covid-19 by the City Government of Makassar with forms of public communication that tend not to answer the need for information during a pandemic to be the primary motivation for this movement. Finally, the Makassar Student and Community Alliance Caring for Covid-19 was created to facilitate society's need for Covid-19. Furthermore, this movement indirectly answers public anxiety regarding health and safety against Covid-19. The activities of this alliance are a concrete manifestation of participatory action by interdisciplinary citizens as a shared educational and information space. Apart from that, this participatory action also shows the great unity and spirit of togetherness that the residents of Makassar City have and their potential, which is very beneficial if empowered collaboratively in action for humanity.